Can the using of SASB standards lead to a reduction in pollution? (المجلة العراقية للعلوم الاقتصادية, 2024)
This study aimed to examine the correlation between the implementation of SASB (Sustainability Accounting Standards Board) standards and pollution levels. Data was collected through a questionnaire administered to a sample of 25 experts specializing in environmental issues and pollution. To ensure the accuracy of the scale, reliability and validity measures were employed, along with calculations of mean and standard deviation. Additionally, various statistical analyses were conducted to explore the associations between the variables in the questionnaire. Ultimately, the findings indicate a significant relationship between the adoption of standards and the reduction of pollution.